Study on Temperature Field Evolution and Frozen Wall Closure Judgment Criteria of Inclined Shaft under Inclined Holes Freezing Condition. (18th May 2022) - Zhang, Chi; Zhang, Yu; Yang, Weihao; Li, Haipeng; Lu, Quan
Abstract : A similarity experiment study is conducted to investigate the evolution characteristics of temperature field and frozen wall closure judgment criteria for the inclined shaft, under inclined holes freezing condition using an adjustable-angle freeze sinking analogous instrument. The changes of temperature and frozen wall thickness with the freezing time in the inclined shaft section, are recorded in real time, and the water pressure of axial and radial hydrological holes are measured. The results demonstrate that the soil temperature change can be divided into three stages under the conditions of salt-water temperature of -32°C and flow rate of 3.18 m/s: rapid cooling before reaching the freezing point, slow cooling in the process of freezing latent heat release, and accelerated cooling and stabilization after freezing latent heat release. The distance from the freezing pipe is the main factor affecting the freezing wall temperature. Affected by the arched arrangement of frozen pipes, the freezing speed in the position of arch crown and arch baseline is slower than the position of wall corner and base plate. A new judgment criterion of frozen wall closure based on the water pressure of the axial hydrological pipe is recommended. In all, this paper has an enlightenment significance for understanding the evolution of the soil temperature field, and predicting the frozen wall closure time in applications of the inclined holes freezing method for the inclined shaft.